Uzbekistan Public Expenditure Review - Izvorski, Ivailo V.; Trushin, Eskender; Appiah-Koranteng, Alex; Varoudakis, Aristomene; Islam, Roumeen; Safarov, Maksudjon; Lord, David; Motohashi, Mitsunori; Ihsan, Ahya; Zorya, Sergiy; Hawkesworth, Ian; Philipsen, Ferry; et al. (World Bank, Washington, DC, 2020)
This Public Expenditure Review (PER) takes stock of fiscal developments and institutions and analyzes the key issues that bear on the level, composition, challenges, and effectiveness of government spending and the stance of fiscal policy. Understanding these issues is essential, as new fiscal pressures are emerging in the process of economic transformation and as citizens demand higher quality of education and other public services. The fiscal reform agenda remains extensive but working on it will provide an opportunity to strengthen the effectiveness of government and boost inclusive economic growth. In the process of ongoing economic transformation, the government is facing several challenges in fiscal policy, for which this PER has developed policy options.